Induction motor performance improvement using a five-level inverter topology and sliding mode controllers - Chaymae Fahassa; Ahmed Abbou; Yassine Zahraoui; Mohamed Akherraz (Institute of Advanced Engineering and Science, 2023)
This research intends to establish a robust vector control (VC) of a 3-ϕ induction motor (IM). The classical 2-level inverter is displaced by a 5-level neutral-pointclamped (NPC) inverter. The 2-level inverter may only supply 8 voltage vectors, while the 5-level NPC inverter can furnish 125 voltage vectors. The objective is to bring about a command voltage vector that converges to the reference voltage vector as closely as possible; hence, guaranteeing a quick response on one hand and improving the dynamic performance on the other hand. A robust sliding mode controller (SMC) structure is used in all regulation loops. Satisfactory results are obtained for various speed zones. The quality and robustness of the global system are tested under resistive torque disturbance, reversal, high, and low-speed ranges in order to prove system stability. All the simulations have been performed under MATLAB/Simulink.